Constance McLaughlin Green papers - Green, Constance McLaughlin, 1897-1975.; Green, Constance McLaughlin, 1897-1975.
Correspondence, drafts, galleys, and page proofs of writings, notes, printed and near-print material, clippings, speeches, and other papers relating primarily to Green's research on the history of Washington, D.C., and the publication of her two-volume Pulitzer Prize-winning book, Washington (1962-1963). Documents social life and conditions, economic policies, racial attitudes, legal standards, and politics in Washington, D.C., during the 19th and 20th centuries. Also includes material pertaining to Project Vanguard, the first American program to launch an artificial satellite into Earth's orbit; New England's contribution to America's economic progress; and urban history especially relating to Holyoke, Mass., and Naugatuck, Conn. Correspondents include Herbert Smith Bailey, Louis Brownlow, M.D.C. Crawford, Charles B. Fahs, John Hope Franklin, John Ihlder, Phineas Indritz, Edward T. James, Charles A. Lindbergh, and David Allan Robertson.
Library of Congress Prints and Photographs Division.
Historian and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bailey, Herbert Smith -- Correspondence; Brownlow, Louis, -- 1879-1963 -- Correspondence; Crawford, M. D. C. -- 1882-1949 -- Correspondence; Fahs, Charles B. -- 1908-1980 -- Correspondence; Franklin, John Hope, -- 1915-2009 -- Correspondence; Ihlder, John, -- 1876-1958 -- Correspondence; Indritz, Phineas, -- 1916-1997 -- Correspondence; James, Edward T. -- Correspondence; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Robertson, David Allan, -- 1880-1961 -- Correspondence; Project Vanguard; African Americans -- Washington (D.C.); Artificial satellites, American; Astronautics -- United States; Cities and towns -- United States; City and town life -- Connecticut -- Naugatuck; City and town life -- Massachusetts -- Holyoke; Law -- Washington (D.C.); Progress -- Economic aspects; Pulitzer Prizes; Rockets (Aeronautics); Holyoke (Mass.) -- History; Naugatuck (Conn.) -- History; New England -- Economic conditions; United States -- Economic conditions; Washington (D.C.) -- Economic conditions; Washington (D.C.) -- Economic policy; Washington (D.C.) -- History; Washington (D.C.) -- Politics and government; Washington (D.C.) -- Race relations; Washington (D.C.) -- Social life and customs; Washington (D.C.) -- Social conditions; Authors; Historians